An exploration of the attitudes that surround and embody those working with children and young people with PMLD. Issue 3 (8th October 2019) - Shipton, Catherine; O'Nions, Chris
Abstract : This article reports on a small‐scale, school‐based enquiry regarding the views and reflections from practitioners working with children and young people who have complex learning needs (termed 'Profound and Multiple Learning Difficulties' (PMLD) in England). The study was built around a series of key questions which enabled the participants to explore their personal and professional thinking around work which is often highly stressful and requires a substantial raft of skills, alongside an orientation which engages fully with the capabilities of the learners.